MENTAL HEALTH APPLICATION PROTOTYPE WITH MACHINE LEARNING AND AUGMENTED REALITY APPLICATION DURING THE COVID-19 PANDEMIC - Royan Dwi Saputra; Mella Aulia Agusty; Jihan Hanifah; Muhammad Rezkyandar; Septa Inda; Abdiansah (Kresnamedia Publisher, 2021)
The Covid-19 pandemic has impacted all aspects of human life, regardless of the impact on mental health. Mental health is an essential issue because many people experience mental health problems, but they are appropriately not resolved. There are many methods in solving mental health problems, but not all of them can reach people due to distance, time, and costs. This study aims to explain the findings regarding an application made to minimize problems, maintain, and improve the mental health of an application called Soodo. The method used in this research is descriptive quantitative. From the findings of this study, this application can help to maintain and improve people's mental health. The results from system user testing (SUS) showed a satisfactory assessment of the Soodo application. From the results of calculations using the (SUS) method, the statistical results of the evaluation of the Soodo application prototype are Excellent or at grade A.